Do attitude towards behavior, subjective norms, and perceived control behavior matter on environmentally friendly plastic purchasing intention? - Wismantoro, Yohan; Susilowati, MG Westri Kekalih (International Journal of Management and Sustainability, 2025)
This study investigates consumer buying intention in environmentally friendly plastic products by hypothesizing that buying intention in environmentally friendly plastic is influenced by attitudes towards behavior, subjective norms, and perceived behavioral control. The primary data used in this research was collected through a questionnaire approach using social media platforms such as Line, Instagram, WhatsApp, and Facebook. The total number of respondents was 114. This study used multiple regression analysis. The results show that attitudes towards behavior and perceived behavioral control positively influence intention in purchasing environmentally friendly plastic products, whereas subjective norms do not. Overall, attitudes towards behavior, subjective norms, and perceived behavioral control significantly influence environmentally friendly plastic purchasing intention. The practical implication is that concrete actions can be taken to use environmentally friendly plastic robustly, such as increasing knowledge of environmentally friendly plastic through various channels, especially social media. To make prices affordable, stakeholders must also develop environmentally friendly plastic with low production costs.